Improving the English literacy skills of Malaysian dyslexic children: the case of culturally responsive mobile multimedia tool - Balamuralithara Balakrishnan; Hor, Beng Chong; Muhamad Zaffwan Idris; Ahmad Nizam Othman; Muhammad Fadhil Wong; Mohamed Nor Azhari Azman (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
Multimedia tools are becoming convenient and efficient exercise medium for dyslexic children who need to do regular language exercises in order to overcome their neurological learning disability. This study examined a newly developed, culturally responsive mobile multimedia tool for learning English among dyslexic children. The tool is an amalgamation of both cultural and linguistic features in the context of learning English among Malaysian dyslexic children who had different phonological process in utilizing audio capturing tool which hampered the development of their literacy skills. The tool was developed for smartphones and tablets that could run in both Android and IOS platforms. We conducted a test to evaluate the effectiveness of the multimedia tool using quasi experimental method among 20 dyslexic children. The outcomes of the evaluation process revealed that the developed mobile multimedia tool improved both writing and reading capability of the participants compared to traditional training method. This provides evidence that the newly developed culturally responsive multimedia tool could substantially benefit dyslexic Malaysian English learners as well as language instructors who train dyslexic students to acquire literacy skills and attain their better learning capability.